Challenges before the achievement of a sustainable cultural tourism - Filipova, Milena (Array, 2008)
Abstract: Tourism as a world culture phenomenon furthers the discovery of various aspects and manifestations of culture. The cultural tourism allows the familiarization with and illustration of the historical development of various civilizations throughout the centuries and the achievements in the various fields of human activities. The tourist travel activates cognitive, informative, communicational and evaluating functions of perception of reality at the place of destination. Each travel brings a new knowledge and a touch to an alien social cultural environment; each tourist, even at a subconscious level, performs a comparative analysis of the alien and of their own culture. Cultural tourism furthers the knowledge, study and comparison of the cultural heritage. The more unique, authentic and valuable it is, the greater is the power of attraction of the corresponding tourism destination. Apart and independent from the expert's evaluation of the cultural heritage qualities and features, its value is influenced also by the nature of tourists' expectations. Therefore from a tourism point of view the greater these expectations are, the higher is the evaluation of the cultural heritage of the corresponding destination